Prevalence of Metabolic Syndrome among the Patients Attending for Master Health Check-up in Family Medicine Department - Pant, Ramesh; Lamsal, Dinesh K; Dahal, Sudip C; Shankhadev, Rajeeb; K C, Deepesh; Panta, Ganga (Journal of Karnali Academy of Health Sciences, 2021)
Introduction: Metabolic syndrome (MetS) is a cluster of conditions that occur together, increasing risk of heart disease, stroke and type 2 diabetes. The prevalence of MetS is increasing worldwide. The aim of the study is to determine the prevalence of MetS among patients attending for Master Health check-up at Family Medicine outpatient department, to find out common component and see the association of body mass index with MetS.Methods: This cross-sectional observational study was done at family medicine outpatient department over a period of six months. There were total of 854 participants involved in the study and each subject was interviewed, anthropometric measured, biochemical parameter recorded in the Performa. The MetS was diagnosed according to modified National Cholesterol Education Program Adult Treatment Panel III (NCEPATP III) criteria.Results: The MetS was diagnosed in 53.9 %( 95% CI:50.56%-57.24%)of the study population on the basis of modified NCEP-ATP III criteria, with prevalence significantly higher among males (58.3%) than in females (48.6%)(P value